2006
DOI: 10.1097/00006223-200611000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Clinical Experience

Abstract: Simulation with high-fidelity technology is an innovative and effective teaching strategy to address increasing student enrollment, faculty shortages, and limited clinical sites. This interactive learning method allows the educator to focus on desired content and teach multiple objectives. This study examines students' perceptions of a preterm labor simulated clinical experience as a method of instruction, emphasizing the importance of the educators' role in promoting positive student outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Evidence from other training fields would suggest that this may be the case. For example, in medical, nursing, and counseling training, research has shown that a wide variety of skills can be taught using computer simulations (Ravert, 2002; Schoening, Sittner & Todd, 2006; Scalese, Obeso, & Issenberg, 2007). Moreover, efforts to train staff using computer simulation alone to teach DTT skills have shown some promise (Eldevik et al, 2010).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Evidence from other training fields would suggest that this may be the case. For example, in medical, nursing, and counseling training, research has shown that a wide variety of skills can be taught using computer simulations (Ravert, 2002; Schoening, Sittner & Todd, 2006; Scalese, Obeso, & Issenberg, 2007). Moreover, efforts to train staff using computer simulation alone to teach DTT skills have shown some promise (Eldevik et al, 2010).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…[7][8][9][10] Mannequin-based clinical simulation education potentially offers nursing students varied clinical patient situations that are comparable with an acute setting. [11][12][13][14][15] Simulation technology provides a risk-free, controlled learning experience that supports the learner's transfer of classroom and skills laboratory knowledge to realistic patient interactions. 16 -19 High-fidelity mannequins are computer-based technologically advanced simulators that are programmed to respond to the learner's action or inaction.…”
Section: Nursing Educationmentioning
confidence: 99%
“…It also included reviewing the literature to prepare a student satisfaction questionnaire and validated scale to determine students' confidence which will be used post-simulation exposure at the end of project to evaluate the perceived effectiveness of scenario-based simulation as a teaching strategy (Abdo & Ravert, 2006, Alinier et al, 2004, Bambini et al,. 2007, Beyca & Kobokovich, 2004, Feingold et al, 2004, Levett-Jones et al, 2011, Mole and McLaffery, 2004, Schoening, 2006. There were study results that support the use of simulation scenarios throughout the undergraduate curriculum because it can be beneficial to enhance student's confidence regarding patient care decisions (Bambini et al, 2007, Beyca & Kobokovich, 2004.…”
Section: Wp 3: Identification Of the Needs Of The Target Groupmentioning
confidence: 99%